En voldtægtsmand på din vej: Performance, aktivisme og erindring under el estallido social i Chile - Thygesen, Alexander Ulrich (K&K - Kultur og Klasse, 2023)
This article studies how the Chilean street performance Un violador en tu camino reorganized what Jacques Rancière calls the distribution of the sensible and simultaneously facilitated the emergence of new collective subjects. Theoretically anchored in Ann Rigney’s memory-activism nexus, it explores the performance’s role as part of an inherited Chilean protest repertoire, while arguing that the performance’s redistribution of the sensible and inherent collectivization of experiences did not only affect contemporary conditions, but also the remembrance of the past. The article demonstrates that Un violador en tu camino is an integrated part of a decades-long tradition of performative activist interventions in the public space in Chile and therefore serves as an example of how activists learn from earlier social movements and repurpose their practices in new contexts of contention. Furthermore, through the analysis of the performance’s lyrics, choreography, visual expression, and placement in the public space, the article concludes that the performance made visible the continuity of state perpetrated sexual violence in Chile: from the military dictatorship to the estallido social protest wave in 2019-2020 that together with the coherent emergence of new collective subjects, united activists from different generations in a multitemporal denouncement of the patriarchy’s abuse.